Effect of experimental fascioliasis on feed intake, nitrogen retention and body weight changes in open and pregnant Menz sheep - Akinbamijo, O.O.; Lahlou-Kassi, A.; Tembely, S. (Elsevier, 1996)
The effect of a sub-clinical fascioliasis infection on feed intake, OM digestibility (OMD), N retention (NRET), rate of BW changes and lamb birth weight was studied in 23 open and 17 pregnant Menz ewes. The infection was imposed by oral dosing with Fasciola hepatica in pregnant and open ewes. All ewes were assigned to four treatment groups: pregnant infected (PI), pregnant non-infected (PC), open infected (OI) and open non-infected (OC). The infected ewes became anaemic from Week 8 post-infection (p.i.) and F. hepatica eggs were first observed in the faeces from Week 11 p.i. During two NRET trials (at ewes voided higher urinary N, resulting in lower NRET at 8 weeks p.i. Infected ewes also had lower weight gains than control ewes. Lambs from infected dams weighed less at birth than lambs from control dams. It was concluded that under the conditions of the present experiment, although subclinical fascioliasis did not affect feed intake or digestibility coefficients, it did reduce the rates of live weight changes, NRET, and lamb birth weight. Consequently, it reduced the overall productivity of infected ewes.